2007
DOI: 10.1021/jp0669557
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Heterogeneous Electrical and Electrochemical Properties of Hydrogen-Terminated Boron-Doped Nanocrystalline Diamond Thin Film Deposited from an Argon-Rich CH4/H2/Ar/B2H6 Source Gas Mixture

Abstract: Spatially heterogeneous electrical and electrochemical properties were observed for hydrogen-terminated, boron-doped nanocrystalline diamond thin-film electrodes by conducting-probe atomic force microscopy (CP-AFM) and scanning electrochemical microscopy (SECM). CP-AFM was used to simultaneously map the topography and electrical conductivity of the film as a function of the boron-doping level and bias voltage. The electrode was characterized by areas of high electrical conductivity separated by regions of low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 55 publications
1
33
1
Order By: Relevance
“…BDD materials are electrically heterogeneous with conductivity and electron-transfer rates varying across the BDD surface. This behavior is also confirmed by microscopic characterization of conductivity and redox activity for both hydrogen- 90 . The extent to which the physicochemical properties of glassy carbon (sp 2 ) and diamond (sp 3 ) carbon electrodes influence the response depends on the mechanistic aspects for the particular redox analyte.…”
Section: Electrochemistry Of Boron-doped Diamond (Bdd)supporting
confidence: 65%
“…BDD materials are electrically heterogeneous with conductivity and electron-transfer rates varying across the BDD surface. This behavior is also confirmed by microscopic characterization of conductivity and redox activity for both hydrogen- 90 . The extent to which the physicochemical properties of glassy carbon (sp 2 ) and diamond (sp 3 ) carbon electrodes influence the response depends on the mechanistic aspects for the particular redox analyte.…”
Section: Electrochemistry Of Boron-doped Diamond (Bdd)supporting
confidence: 65%
“…It has been reported that the current distribution is observed in SG-TC images for a BDD surface with a Ru(NH3)6 3+ mediator. [5][6][7] Our result is clearly different from the previously reported SECM images for a BDD substrate, because these current distributions for BDD substrates mainly reflect the bulk conductivity distribution, which is caused by the hole density difference derived from the boron concentration. Figure 5(C) indicates the results of line scanning, which results from changing the substrate potential by using 1 mM of the Fe 2+ mediator.…”
Section: Secm Negative Feedback Mode and Sg-tc Mode Imaging For Pattecontrasting
confidence: 99%
“…3,4 This SECM technique has recently been applied to the imaging of local electrochemical activity on carbon materials, such as borondoped diamond (BDD). [5][6][7] The Bard and Swain groups have reported the local electrochemical activity on low boron-doped diamond electrodes attributed to a crystal region and a grain boundary layer. 5 With BDD, the density of holes, which are major charge carriers in BDD, is different for each crystal facet because the boron uptake depends on the crystal growth facets.…”
Section: Introductionmentioning
confidence: 99%
“…It was postulated that the response could be dominated by a network of electrochemically active NDC inclusions, most probably residing at grain boundaries, within a less-active diamond matrix [100]. Alternate theories questioned the role boron doping density and local DOS played in controlling ET in BDD [71,118]. However, pioneering work with single crystals and electrochemical imaging techniques, the latter where it is possible to probe the electrochemical response on a grain by grain basis, has now irrefutably demonstrated that BDD itself is capable of transferring electrons, albeit at a slightly slower rate (for an outer-sphere redox species) compared to a classical metal electrode.…”
Section: Polycrystalline Versus Single-crystal Electrochemistrymentioning
confidence: 99%
“…SECM SG-TC images (tip size 2 μm) and C-AFM images were also recorded on H-terminated NC BDD thin-film electrodes, grain size 15-20 nm, of different dopant densities in the range of approximately 0 to mid-10 20 B atoms cm −3 [118]. For the undoped NC electrodes, C-AFM revealed a number of conducting pathways, attributed to NDC content at grain boundaries, a conclusion also reached by Figure 5.14 (a) Schematic illustrating SECM SG-TC mode.…”
Section: Electrochemical Imaging Of Polycrystalline Bddmentioning
confidence: 99%